The ecophysiological response of Bombax ceiba L. to soil of industrial areas - Kabir, Muhammad; Iqbal, Muhammad Zafar; Shafiq, Muhammad; Farooqi, Zia-ur-Rehman (Journal of Forests, 2023)
The knowledge about the ecology and relationship among plant-soil is required to increase the vegetation cover around the industrial units. However, no information is available about this aspect on seedling growth performance of commercially important timber tree, B. ceiba. This study was designed with the purpose to record the effects of soil of different industrial areas on seedling growth performances of B. ceiba in pot culture. The comparison of the results showed variable effects on plant height, cover, leaf size, seedling dry and fresh weight of B. ceiba raised in different industrial soil variably affected due to industrial activities. The assessment with the treatment of soils of Universal Chemicals showed maximum reduction in plant height and leaf area of B. ceiba. The treatment of National Foods Ltd. soil positively increased the growth for B. ceiba, as it may contain more nutrient supply required for proper growth of B. Ceiba. It was concluded that the soil of Universal Chemicals factory was found less favorable for growth variables of B. ceiba. The findings suggests that the plantation of B. ceiba around the industrial units would be helpful in increasing the vegetation cover.